The suffering servant Isaiah 53 for the life of the Church - McConville, J. G. 1950- (Grand Rapids, Michigan Baker Academic, a division of Baker Publishing Group, 2023)
"Offers an exposition of Isaiah 53, showing how this classic and beloved text can speak afresh to the life of the church today"--
Includes bibliographical references (pages 187-191) and indexes
Keywords: Bible -- Commentaries; Servant of Jehovah